Existence and Multiplicity of Solutions for Anisotropic Discrete Boundary Value Problems Involving the ($p_1(t)$, $p_2(t)$)-Laplacian (Journal of Nonlinear Modeling and Analysis, 2025)
For an anisotropic discrete nonlinear problem with a variable exponent, we demonstrate both the existence and multiplicity of nontrivial solutionsin this study. Our technique is based on variational methods.